Archaeometric investigation of the Hellenistic period Colchian amphoras from Pichvnari (Western Georgia) - Rogava, Andria; Kibaroglu, Mustafa; Khalvashi, Merab (Revista Arheologică, 2026)
The article presents a first extensive archaeometric (macroscopic and petrographic) analysis of the Hellenistic period Colchian “brown-clay” amphoras discovered at Pichvnari, one of the most representative sites for the study of this type of transport containers. The material consists of 44 amphora and 3 sand samples taken for comparative reasons in the broad surrounding of the site. The macroscopic fresh break and petrographic thin section analysis is set in the context of previous work done by other authors. The Pichvnari material reveals various fabric recipes that largely correspond to the already determined fabric groups. However, in contrast to the previous works, the study also manages to show the compositional profiles of the fabric groups in a greater detail and therefore supposes the possibility of a minor fabric variations eventually linked to sub-regional productions. Mineralogical comparison with the sand samples allows us to carefully suppose that the tempering material originated in the riverine and/or coastal sedimentary environment in the area around Pichvnari. However, due to the lack of a more extensive and systematic raw material sample collection from the region of interest, the question of the exact provenance of Pichvnari “brown-clay” amphoras remains open.